2015
DOI: 10.1007/s10147-015-0810-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of duloxetine in Japanese patients with chemotherapy-induced peripheral neuropathy: a pilot randomized trial

Abstract: Our data suggests that duloxetine has a beneficial effect on CIPN caused by oxaliplatin, paclitaxel, vincristine, or bortezomib in Japanese patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(64 citation statements)
references
References 18 publications
2
61
0
1
Order By: Relevance
“…Additionally, there are no medications currently available for the prevention of CIPN in patients undergoing treatment with neurotoxic chemotherapeutic agents . For patients who are experiencing CIPN, the antidepressant, duloxetine, is recommended although the magnitude of benefit is modest and much less than is desirable . In several case series, pregabalin reportedly alleviated CIPN with a relatively good safety profile .…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, there are no medications currently available for the prevention of CIPN in patients undergoing treatment with neurotoxic chemotherapeutic agents . For patients who are experiencing CIPN, the antidepressant, duloxetine, is recommended although the magnitude of benefit is modest and much less than is desirable . In several case series, pregabalin reportedly alleviated CIPN with a relatively good safety profile .…”
Section: Introductionmentioning
confidence: 99%
“…A 2013 double-blinded, placebo-controlled, crossover trial found that duloxetine 60 mg daily had a beneficial effect on CIPN-related pain 52 . These findings were more recently confirmed in a study comparing duloxetine 40 mg daily and vitamin B12 53 .…”
Section: Treatmentmentioning
confidence: 60%
“…Recently, we reported the results of an open-label, pilot randomised trial wherein duloxetine was compared with vitamin B 12 in Japanese patients with CIPN. 8 Significant differences in improvement in numbness and pain were observed in the duloxetine group in comparison with those in the vitamin B 12 group. Adverse events (AE) including fatigue, somnolence, insomnia and nausea were observed, but all were grade 1 in common terminology criteria for AE (CTCAE) V.4.0.…”
Section: Discussionmentioning
confidence: 89%